1990
DOI: 10.1007/bf00030037
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fertilizer, soils, and site preparation influence loblolly pine productivity

Abstract: Application.Forest managers wishing to rapidly produce large individual pole-size loblolly pine trees should consider phosphorus fertilization with mechanical site preparation prior to planting on Udult Ultisols. If maximizing total stand volume is the primary objective, no simple recommendations can be made because of the confounding effects of soil types and site preparation methods on stand survival and yield. Fertilizer recommendations for maximizing total stand volume will have to be made on a case by cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…Previous research has documented the positive effects of fertilization on plantation loblolly pine aboveground productivity (Vose and Allen, 1988;Colbert et al, 1990;Haywood and Burton, 1990;Haywood and Tiarks, 1990;Dalla-Tea and Jokela, 1991;Haywood et al, 1997;Albaugh et al, 1998;Jokela and Martin, 2000;Borders and Bailey, 2001;Retzlaff et al, 2001;Samuelson et al, 2001). We also found that fertilization increased aboveground stand productivity.…”
Section: Stand Productivitysupporting
confidence: 78%
“…Previous research has documented the positive effects of fertilization on plantation loblolly pine aboveground productivity (Vose and Allen, 1988;Colbert et al, 1990;Haywood and Burton, 1990;Haywood and Tiarks, 1990;Dalla-Tea and Jokela, 1991;Haywood et al, 1997;Albaugh et al, 1998;Jokela and Martin, 2000;Borders and Bailey, 2001;Retzlaff et al, 2001;Samuelson et al, 2001). We also found that fertilization increased aboveground stand productivity.…”
Section: Stand Productivitysupporting
confidence: 78%
“…Most long-term site preparation studies in the southern USA have confounded burning with mechanical treatment making it impossible to evaluate the specific effect of burning (Vitousek and Matson, 1985;Haywood and Burton, 1990;Anonymous, 1991;Edwards, 1994;Miller et al, 1995;Tiarks and Haywood, 1996). Since the introduction of imazapyr-type herbicides (Shaner and O'Connor, 1991), aerial application of chemicals has replaced mechanical treatment for control of woody competition in pine plantations.…”
Section: Fire Effects On Species Composition and Competitionmentioning
confidence: 99%
“…Ruston (fine-loam, siliceous, thermic Typic Paleudult), Kirvin (clayey, mixed, thermic, Typic Hapludult), Henry (coarse-silty, mixed, thermic Typic Fragiaqualf), Sawyer (fine-silty, siliceous, thermic Aquic Paleudult) and Boswell (fine, mixed, thermic Vertic Paleudalf), respectively, were the representative series for the 5 textural classes. Detailed descriptions of the soils present on these study sites are found in Haywood and Burton (1990).…”
Section: Study Sitesmentioning
confidence: 99%
“…Each experimental plot was then split into 43.9 X 15.2 m (667 m') fertilized and 43.9 X 3 1.1 m (1,365 m') unfertilized portions. The fertilization treatment consisted of a single surface broadcast application of 168 kg P205 triple superphospate/ha (73.4 kg P/ha), prior to planting loblolly pine seedlings (Haywood and Burton 1990).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%